A política dos algoritmos e a economia das máquinas: uma etnografia sobre o sistema peer-to-peer Bitcoin - Cardoso, Bruno Campos (2024)
This thesis describes the socio-technical relationships that constitute the digital systems of cryptocurrencies from the interfaces of the anthropology of finance and the anthropology of science and technology. Based on ethnographic material collected and elaborated between 2017 and 2020, such as documents and digital artifacts, in discussion groups, forums, email lists, public software development platforms and interviews, the present work describes the main algorithmic procedures and political-material economies that underpin cryptocurrencies as distributed or decentralized electronic cash systems. By taking the first of these cryptocurrencies, the peer-to-peer Bitcoin system, as the main object of analysis, I reflect on the techno-financial relations of the so-called players – humans and machines involved in establishing digital property transaction systems, value speculation and distributed ledger data structures. The thesis aims to offer a description of the relationships, actors and socio-technical systems surrounding Bitcoin in order to highlight the political-economic effects of the circulation of cryptocurrencies on the formation of markets and infrastructures on which digital assets are established. I also explore the imaginations of the future that arise from the development of financial instruments, new modes of transaction and the technocratic and neoliberal ideologies whose principles are, more or less explicitly, encoded in software.